2015
DOI: 10.1093/infdis/jiv132
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Marburg Virus Transmission From Experimentally Infected to Susceptible In-Contact Egyptian Fruit Bats

Abstract: Egyptian fruit bats (Rousettus aegyptiacus) were inoculated subcutaneously (n = 22) with Marburg virus (MARV). No deaths, overt signs of morbidity, or gross lesions was identified, but microscopic pathological changes were seen in the liver of infected bats. The virus was detected in 15 different tissues and plasma but only sporadically in mucosal swab samples, urine, and fecal samples. Neither seroconversion nor viremia could be demonstrated in any of the in-contact susceptible bats (n = 14) up to 42 days aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(115 citation statements)
references
References 21 publications
7
103
4
1
Order By: Relevance
“…However, virus was not detected in feces or urine collected from infected specimens or the cave floor (Amman et al 2012). Laboratory experimental subcutaneous infection of R. aegyptiacus identified a number of PCR-positive tissues including salivary glands in asymptomatic bats and viral loads detected in oral and rectal swabs are consistent with biting as a mode of bat-bat transmission (Amman et al 2015;Paweska et al 2015). However, the period during which the virus could be isolated was limited to a few days, and no transmission from the infected specimens to naïve, incontact conspecifics could be induced.…”
Section: Evidence Of Link Between Fruit Bats and Marburg Virusesmentioning
confidence: 77%
See 1 more Smart Citation
“…However, virus was not detected in feces or urine collected from infected specimens or the cave floor (Amman et al 2012). Laboratory experimental subcutaneous infection of R. aegyptiacus identified a number of PCR-positive tissues including salivary glands in asymptomatic bats and viral loads detected in oral and rectal swabs are consistent with biting as a mode of bat-bat transmission (Amman et al 2015;Paweska et al 2015). However, the period during which the virus could be isolated was limited to a few days, and no transmission from the infected specimens to naïve, incontact conspecifics could be induced.…”
Section: Evidence Of Link Between Fruit Bats and Marburg Virusesmentioning
confidence: 77%
“…Evidence for a filovirus-fruit bat link is stronger for Marburg virus (MARV), although knowledge gaps regarding the full host range and circulation also remain for this filovirus Towner et al 2009;Amman et al 2012;Paweska et al 2015;reviewed in Olival and Hayman 2014). Virological studies focused on R. aegyptiacus inhabiting East African caves where MARV outbreaks occurred, found live, healthy specimens of R. aegyptiacus to be MARV PCR and seropositive.…”
Section: Evidence Of Link Between Fruit Bats and Marburg Virusesmentioning
confidence: 99%
“…Serological studies of virus-specific bat antibodies were among the first functional studies to be performed. Infection of R. aegyptiacus with MARV resulted in the development of antigen-specific IgG responses in the bats by 28 days after challenge (25,(109)(110)(111). While the durability of the antibody response seems to vary-with one study reporting that antibody titers fell below detectable levels by 3 months after infection (25) and another study finding virus-specific IgG levels were still maintained 11 months following infection (111)-both studies found that secondary challenge with MARV increased virus-specific IgG antibodies titres to a greater extent than seen following initial MARV infection.…”
Section: Antibody Responses In Batsmentioning
confidence: 99%
“…Similar results were documented with the Egyptian rousette bats infected with MARV, where replication occurred but overt signs of illness were absent. Notably, this same bat species was demonstrated to be refractory to experimental infection with EBOV (30)(31)(32).…”
mentioning
confidence: 99%